ATTITUDE TOWARDS GENDER EQUALITY: A COMPARATIVE STUDY IN ADOLESCENTS IN THE CITY OF AREQUIPA, PERU - Julio C. Huamani-Cahua; Alison Serruto-Castillo; Víctor Alfonso Rivera-Flores; Aguilar-Del Carpio Carlos Ilich (Universidad Ciencia y Tecnología, 2020)
This study compares and explains the attitude towards gender equality in 319 adolescents aged 15 to 17, of both sexes, from three public educational institutions in the city of Arequipa, Peru that were selected in a way intentional. The instrument used was the Gender Equality Attitudes Questionnaire (CAIG), assesses six factors and presents high reliability indices. The results indicate that there are more favorable attitudes towards gender equality in women than in men, the factors being values and structure of the couple and the public sphere factor, where the differences are moderate, in the other factors the differences are minimal. There are no differences in the variable under study with respect to age or religious belief, however, there seems to be minimal sexual orientation in younger adolescents with a Catholic religion. Finally, the variable that best explains the attitude towards gender equality is sex, where women have an average of 11.9 times more than men having a favorable attitude towards gender equality adjusted for age and religion.Keywords: Gender equality, attitude, adolescents.References[1]S. Galdos, «La conferencia de El cairo y la afirmación de los derechos sexuales y reproductivos, como base para la salud sexual y reproductiva.,» Revista Peruana de Medicina Experimental y Salud Pública, vol. 30, nº 3, pp. 445-460, 2013.[2]R. García, M. Rebollo, O. Buzón, R. Gonzales, R. Barragán and E. Ruiz, «Actitudes del alumnado hacia la igualdad de género,» Revista de Investigación Educativa, vol. 28, nº 1, pp. 217-232, 2010.[3]V. Acuña, «Conversación juvenil e identidad de género: despliegues de feminidad heterosexual en grupos de jóvenes veinteañeras,» Círculo de Lingüística Aplicado a la Comunicación, vol. 69, pp. 3-33, 2017.[4]J. Piedra, R. García, E. Fernández and M. Rebollo, «Brecha de género en educación física: actitudes del profesorado hacia la igualdad,» Revista Internacional de Medicina y Ciencias de la Actividad Física y el Deporte, vol. 14, nº 53, pp. 1-21, 2014.[5]I. Lozano, «Mujeres de ETA: lectura de sus representaciones en el discurso.,» Cuestiones de Género:de la Igualdad y la Diferencia, vol. 11, pp. 37-55, 2016.[6]C. Rey, «Habilidades pro sociales, rasgos de personalidad de género y aceptación de la violencia hacia la mujer, en adolescentes que han presenciado violencia entre sus padres.,» Acta Colombiana de Psicología, vol. 11, nº 1, pp. 107-118, 2008.[7]C. Silva, J. Mendoza and K. González, «Varones adolescentes: Rol de género y actitudes hacia el peso y la alimentación.,» Revista Mexicana de Psicología, vol. 31, nº 1, pp. 50-57, 2014.[8]A. Rebollo, E. Ruiz and R. García, «Preferencias relacionales en la adolescencia según el género,» Revista Electrónica de Investigación Educativa, vol. 19, nº 1, pp. 58-72, 2017.[9]A. Martos, M. Simón, A. Barragán, M. Molero, M. Pérez and J. Gázquez, «Revisión del uso de las nuevas tecnologías para la intervención en violencia de género en parejas de adolescentes,» European Journal of Child Development, Education and Psychopathology, vol. 4, nº 1, pp. 63-73, 2016.[10]A. De Sola, I. Martínez and J. Meliá, «El cuestionario de actitudes hacia la igualdad de género (CAIG): elaboración y estudio psicométrico.,» Anuario de Psicología, vol. 34, nº 1, pp. 101-123, 2003.